Respuesta :
4(-x+4)=12 (You have to use distribution first)
-4x+16=12 (Then, you subtract 16 from both sides)
-4x=-4 (Finally, you have to divide the -4 that's besides x by both sides)
x=1
-4x+16=12 (Then, you subtract 16 from both sides)
-4x=-4 (Finally, you have to divide the -4 that's besides x by both sides)
x=1
4(-x + 4) = 12
Follow PEMDAS. In this case, because you cannot add -x and 4 (x being a variable (changeable number), you distribute 4 to both -x and 4
4(-x) = -4x
4(4) = 16
-4x + 16 = 12
Because of the equal sign, what you do to one side you do to the other.
Isolate the x, subtract 16 from both sides
-4x + 16 (-16) = 12 (-16)
-4x = 12 - 16
-4x = -4
Isolate the x, divide - 4 from both sides
-4x/-4 = -4/-4
x = -4/-4
x = 1
1 is your answer.
hope this helps
Follow PEMDAS. In this case, because you cannot add -x and 4 (x being a variable (changeable number), you distribute 4 to both -x and 4
4(-x) = -4x
4(4) = 16
-4x + 16 = 12
Because of the equal sign, what you do to one side you do to the other.
Isolate the x, subtract 16 from both sides
-4x + 16 (-16) = 12 (-16)
-4x = 12 - 16
-4x = -4
Isolate the x, divide - 4 from both sides
-4x/-4 = -4/-4
x = -4/-4
x = 1
1 is your answer.
hope this helps